Penelitian Agama: Sebuah Pengantar - Tamam, Ahmad Badrut (MADINAH, 2016)
Language research is derived from the word "meticulous", which means "meticulous" or "thorough". Research means the same as "investigation" or "examination" is done carefully and thoroughly. The term research is a translation of English "research" which means a business or job to seek back that is done by a certain method and in a careful, systematic and perfect way to the problem, so that it can be used to solve or answer the problem. So, in general, research can be interpreted as an attempt to find a responsible answer to a number of problems based on data collected through scientific, systematic, controlled, empirical and critical procedures. Since the era of the 70s, religious and religious observers in Indonesia are anxious over the methodology in religious and religious research. At that time, religious and religious research using methods commonly used in scientific research for academic purposes, is still considered to be percussive. According to Amin Abdullah, such phenomena are not only happening in Indonesia alone, but also appear in the Western world. Arkoun called it taqdis al-afkar ad-diniy (sacred religious thought).